Researchers' Career Transitions over the Life Cycle - Daiji Kawaguchi; Ayako Kondo; Keiji Saito (Institute for the Study of Labor (IZA), 2016)
Based on a unique time-use survey of academic researchers in Japan, this study finds that research time decreases over the life cycle. The decrease in total hours worked and the increase in time spent on administrative tasks explain the decrease in research time. We also show that the decrease of research time partly explains why the research output of older researchers' decreases. The results suggest that proper incentives and job designs for senior researchers may increase their research output.
Keywords: J22; J24; J44; 330; researchers' time use; research output; academic researchers; academic administration; education; multi-tasking